Are in vitro cytotoxicity assessments of environmental samples useful for characterizing the risk of exposure to multiple contaminants at the workplace? - Viegas, Carla (2022)
Funding Information: This work was supported by Instituto Polit?cnico de Lisboa, for funding the Project ?Occupational exposure of ambulance drivers to bioburden? (IPL/2020/BIO-AmbuDrivers_ESTeSL). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.